Stage and disease‐free interval help select patients for surgical management of locally recurrent and metastatic adrenocortical carcinoma. Issue 2 (6th December 2019) - Lo, Winifred; Ayabe, Reed I.; Kariya, Christine M.; Good, Meghan L.; Steinberg, Seth M.; Davis, Jeremy L.; Ripley, Robert T.; Hernandez, Jonathan M.
Abstract: Background and Objectives: Chemotherapeutic options for patients with recurrent/metastatic adrenocortical carcinoma (ACC) are limited, leading to consideration for surgical management. We sought to determine characteristics associated with an unequivocal survival benefit amongst patients undergoing re‐resection or metastasectomy. Methods: Patients who underwent surgery for recurrent/metastatic ACC were identified and stratified into two groups: those with postoperative survival comparable with what has been reported with chemotherapy alone (<12 months) and those surviving twice that duration (>24 months). Those who survived between 12 and 24 months were excluded, as the objective was to characterize patients who most distinctly benefited from resection. Clinicopathologic and treatment variables were evaluated for associations with survival. Results: Forty‐three patients survived more than 24 months and 15 patients died less than 12 months after reoperation. Tumor stage (odds ratio [OR], 0.66; 95% confidence interval [CI], 0.45‐0.96) and disease‐free interval (DFI; OR, 3.23; 95% CI, 1.68‐6.22) were associated with prolonged survival. Tumor size, hormonal status, resection margin, and treatment with chemotherapy, radiation, and mitotane were not associated with prolonged survival. Patients who survived more than 24 months underwent more procedures for subsequent recurrences (median 4 vs 2; P  < .001). Conclusion: Stage and DFI can help select optimal candidates for resection of recurrent/metastatic ACC. Patients selected for surgical management should be informed of the likelihood of requiring multiple interventions.